Cooperative takaful for non-banking financial institutions: Islamization of SOCSO in the case of Malaysia - Mohd Noor, Azman; Abd Rahman, Muhammad Abd Hadi (IIUM Press, 2016)
By the introduction of Takaful as an alternative for conventional insurance in the early 1980s and with more than 30 year experience in Islamic Banking and Finance, it is time for Malaysia to make a move in completing its Islamic financial ecosystem by islamizing non-Banking Financial Institutions. This paper aims to investigate a potential approach to apply the concept of cooperative Takaful in transforming the Social Security Organization (SOCSO) into a Shariah-compliant institution using the concept of cooperative Takaful by emphasizing the similarity between current practices of SOCSO and cooperative Takaful. This paper highlights the difference between normal Takaful and cooperative Takaful. This paper proposes that the cooperative Takaful i.e. Musharakah Ta’awuniyyah model to aid the integration and transformation of SOCSO into a Shariah compliant institution. The contribution of this paper is twofold: First, this paper contributes to the existing literature on application of Musharakah Ta’awuniyyah as another alternative for the Takaful model. Second, it provides the possibility for SOCSO to convert its operation to Shariah compliant concept.